If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 2) = 4(x + 20) Reorder the terms: 6(2 + x) = 4(x + 20) (2 * 6 + x * 6) = 4(x + 20) (12 + 6x) = 4(x + 20) Reorder the terms: 12 + 6x = 4(20 + x) 12 + 6x = (20 * 4 + x * 4) 12 + 6x = (80 + 4x) Solving 12 + 6x = 80 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + 6x + -4x = 80 + 4x + -4x Combine like terms: 6x + -4x = 2x 12 + 2x = 80 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + 2x = 80 + 0 12 + 2x = 80 Add '-12' to each side of the equation. 12 + -12 + 2x = 80 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 80 + -12 2x = 80 + -12 Combine like terms: 80 + -12 = 68 2x = 68 Divide each side by '2'. x = 34 Simplifying x = 34
| (180-x)+35=90 | | p=r+s-7 | | -11(3m-9n+2p)= | | 3x+16=x+52 | | -x^2+x-3=0 | | 2x^3-23x^2+25x+50=0 | | 8+6w=160 | | -4(4y-6)+3(3y+8)= | | 5t+8(1.8-t)=12 | | 180=x+55+90 | | 5t+12(1.8-t)=8 | | -9x+5=x-3 | | -5z-12+20z=-11.4+15.6z | | 5(x+6)=3(x+14) | | 180-x=35+90+35 | | 25y^4+20y^2+3=0 | | 5y^4-7y^2-24=0 | | 10x+20=3x | | a^4+64a^2+63=0 | | n+27=-45 | | 14.62+0.07x=15.12-0.09 | | -9(x+4)+2x+5=8x+7 | | 12x-6=-40 | | 14+27x=35+20x | | 4x-12+x=4x-1 | | -4(2t+6)=-40 | | 4(f-4)=-36 | | 15x^2-2-7x=0 | | x+2=97 | | 8(x+1)=4+x | | 10(s-8)=-158 | | 8(x+1)=4-x |